A rheological behavior of various polyvinylidene difluoride binders for high capacity LiNi0.6Mn0.2Co0.2O2. Issue 7 (21st March 2016) - Biso, Maurizio; Colombo, Roberta; Uddin, Md‐Jamal; Stanga, Milena; Cho, Sung‐Jin
Abstract : Various polyvinylidene difluorides (PVDF) as polymeric binding agent in lithium‐ion battery were rheologically evaluated on high capacity and excess lithium‐LiNi0.6 Mn0.2 Co0.2 O2 (Ni‐rich NMC). We found that the suspension polymerized PVDF binder is more stable upon gelation for long duration while other high molecular weight PVDF binders (MW > 900, 000) show irreversible rheological transformation that can dramatically compromise the coating step during lithium‐ion battery electrode slurry preparation. POLYM. ENG. SCI., 56:760–764, 2016. © 2016 Society of Plastics Engineers